THE STUDENTS’ PERCEPTION TOWARD USING MOBILE TECHNOLOGY FOR LEARNING ENGLISH: THE STUDENTS’ PERCEPTION TOWARD USING MOBILE TECHNOLOGY FOR LEARNING ENGLISH - Novarita Novarita (Universitas Muhammadiyah Kotabumi, 2021)
The aim of this study is to find out the students’ perception toward using mobile technology for learning at Baturaja University. This study used the qualitative descriptive research design. The writer conducts 78 students as population of English Education Study Program. The writer only took 65 students as the sample by applying purposive sampling. The data was collected through the students’ perception questionnaire. Then the writer used descriptive statistics analysis technique using SPSS for analyzing the data based on percentage and frequency distributions. The results showed that overwhelming number of university had perceived usefulness and perceived ease of use toward the use of mobile technology for learning English. Majority of university students agreed that mobile technology was useful and easy to use for learning English. The findings indicated that students had high agreement interpretation on the using of mobile technology in perceived usefulness and ease of use to access mobile technology for learning English